2023
DOI: 10.1002/eqe.3842
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of rocking mechanism of shallow foundations on sand via PIV technique

Abstract: Adoption of the rocking isolation concept in foundation design is considered as an effective method in reducing seismic loads of structures. Despite much research conducted on the rocking behavior of foundations, concerns regarding the practical application of the rocking foundation design concept still prevail. The concerns primary stem from the lack of accurate understanding and knowledge associated with the soil‐foundation deformation mechanisms during rocking motions. Determination of deformation mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Consequently, to account for the impact of uplift on the rocking response, other researchers made substantial efforts. Particle image velocimetry was used by Moradi et al (2023) [49] to investigate the deformation mechanisms beneath shaking foundations. They found that during loading cycles, foundations with larger FSv have less contact area with the earth, which causes visible rise on the unloaded side (heel side).…”
Section: Numerical Studies and Computer Visionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, to account for the impact of uplift on the rocking response, other researchers made substantial efforts. Particle image velocimetry was used by Moradi et al (2023) [49] to investigate the deformation mechanisms beneath shaking foundations. They found that during loading cycles, foundations with larger FSv have less contact area with the earth, which causes visible rise on the unloaded side (heel side).…”
Section: Numerical Studies and Computer Visionmentioning
confidence: 99%
“…Kawashima and Hosoiri (2003) [52] conducted a study on the inelastic rocking response of large, rigid foundations. Their findings revealed that rigid foundations do not undergo overturning, even when exposed to ground motions with accelera- Particle image velocimetry was used by Moradi et al ( 2023) [49] to investigate the deformation mechanisms beneath shaking foundations. They found that during loading cycles, foundations with larger FS v have less contact area with the earth, which causes visible rise on the unloaded side (heel side).…”
Section: Numerical Studies and Computer Visionmentioning
confidence: 99%
See 1 more Smart Citation
“…These shape differences arise from variations in the soil-foundation contact area and the degree of toe (loaded side) penetration into the subgrade during rocking. Moradi et al [52] studied the deformation mechanisms beneath rocking foundations using the PIV technique. They found that foundations with large FSv have a smaller contact area with the soil during loading cycles, resulting in a notable uplift on the heel side (unloaded side).…”
Section: Shape Of the Moment-rotation Diagramsmentioning
confidence: 99%